A comparative study on disinfection effect of three different disinfectants for oral dental chair water lines (三种不同消毒剂对口腔综合治疗台水路消毒效果的比较) - WANG Wenjuan (王文娟); LI Yajuan (李雅娟); LI Pei (李培); KONG Li (孔莉); WANG Ting (王婷) (中西医结合护理)
Objective To compare the disinfection effect of three different disinfectants for oral dental chair water lines (DUWLs). Methods Selection of seven independent water source integrated treatment tables in the Stomatology Department of Beijing No. 2 Hospital before opening of the clinic in 2019, divided into 4 groups (3 experimental + 1 control). The experimental group used 500mg/L chlorine-containing disinfectant respectively (2 integrated treatment chairs in group A)、3% hydrogen peroxide (Group B, 2 comprehensive treatment chairs)、60 g/L silver ion peroxide disinfectant (2 comprehensive treatment chairs in group C) and purified municipal water purified water (1 comprehensive treatment chair in control group D). The DUWLs were disinfected by three different disinfectants, and then water samples from each group of triple lances and high-speed hand pieces were collected for bacterial cultures. To compare the total number of bacterial colonies in each group of DUWLs before disinfection and immediately, 1d, 3d, and 7d after disinfection. Results The bacterial colony counts of pre-disinfection DUWLs had exceeded the standard ( all＞4500 cfu/mL). The total number of bacterial colonies of the three disinfectants immediately after disinfection and 1 day after disinfection decreased remarkably, and were lower than that of the pre-disinfection and control group. Three days after disinfection, except for experimental group C, the total number of bacterial colonies in experimental groups A and B exceeded the standard for oral healthcare water as stipulated in the Beijing "Technical specification for the disinfection of water circuits in comprehensive oral treatment tables (DB11_T 1703-2019)". The total number of bacterial colonies in groups A, B and C were close to or exceeded the pre-disinfection level 7 days after disinfection. Conclusion Short duration of time to maintain the effect of 500 ml/L chlorine disinfectant and 3% hydrogen peroxide disinfectant on waterway disinfection. Long-term use causes irreparable damage to the inner wall of the pipeline. Silver ionic disinfectant with 60 g/L hydrogen peroxide was optimal in controlling the total number of bacterial colonies and inhibiting bacterial growth time in oral dental chair water lines (DUWLs). (目的 比较3种不同消毒剂对口腔综合治疗台水路(DUWLs)的消毒效果。方法 选取本院2019年装修后待开诊前7台采用独立水源的综合治疗台, 分为4组(3组实验组+1组对照组), 实验组分别采用500 mg/L含氯消毒剂(A组2台综合治疗椅)、3%过氧化氢(B组2台综合治疗椅)、60 g/L过氧化氢银离子消毒剂(C组2台综合治疗椅)和净化后市政用水纯水(D组对照组1台综合治疗椅), 通过3种不同的消毒剂对DUWLs进行消毒, 然后收集各组三用枪和高速手机水样进行细菌培养, 比较各组DUWLs消毒前及消毒后即刻、1d、3d、7d细菌菌落总数。结果 消毒前DUWLs各组细菌菌落总数均严重超标(均＞4500 cfu/mL)。3种消毒剂消毒后即刻和消毒后1 d细菌菌落总数明显下降, 低于消毒前及对照组。消毒后3 d, 除实验C组外, 实验A、B两组细菌菌落总数均超过北京市《口腔综合治疗台水路消毒技术规范(DB11/T 1703-2019)》规定的口腔医疗卫生用水标准。消毒后7 d, A、B、C三组细菌菌落总数均接近或超过消毒前水平。结论 500 mg/L含氯消毒剂和3%过氧化氢消毒剂对水路消毒效果维持时间短, 长期使用对管路内壁造成不可修复的危害。60g/L过氧化氢银离子消毒剂在控制口腔牙椅水路(DUWLs)细菌落数总数和抑制细菌生长时间方面效果最优。)